Sphingosine-1-phosphate in the regulation of diabetes mellitus: a scientometric study to an in‐depth review - Li, Jieying; Fan, Yongfu; Tu, Wenling; Wu, Linyue; Pan, Yun; Zheng, Mingze; Qu, Yiqian; Cao, Lingyong (Frontiers in Endocrinology, 2024)
Diabetes is a significant global health issue, causing extensive morbidity and mortality, and represents a serious threat to human health. Recently, the bioactive lipid molecule Sphingosine-1-Phosphate has garnered considerable attention in the field of diabetes research. The aim of this study is to comprehensively understand the mechanisms by which Sphingosine-1-Phosphate regulates diabetes. Through comprehensive bibliometric analysis and an in-depth review of relevant studies, we investigated and summarized various mechanisms through which Sphingosine-1-Phosphate acts in prediabetes, type 1 diabetes, type 2 diabetes, and their complications (such as diabetic nephropathy, retinopathy, cardiovascular disease, neuropathy, etc.), including but not limited to regulating lipid metabolism, insulin sensitivity, and inflammatory responses. This scholarly work not only unveils new possibilities for using Sphingosine-1-Phosphate in diabetes treatment but also offers fresh insights and recommendations for future research directions to researchers.